Changing Trends of Software for Profitability in 5-Star Hotels (Global Journal of Management and Business Research, 2022)
Because the hotel sector is very competitive, it is vital to not only stay up with the latest technology developments, but also to move with the times. Because consumer expectations and requirements are always altering, keeping your finger on the pulse is especially important in the context of COVID.
Keywords: covid 19; hospitality; tourism; software